Does the parasite-mediated selection drive the MHC class IIB diversity in wild populations of European chub (Squalius cephalus) - Seifertová, Mária; Jarkovský, Jiří; Šimková, Andrea (Parasitology research, 2016)
The genes of major histocompatibility complex (MHC) provide an excellent opportunity to study host-parasite relationships because they are expected to evolve in response to parasites and variation in parasite communities. In this study, we investigated the potential role of parasite-mediated selection acting on MHC class IIB (DAB) genes in European chub (Squalius cephalus) natural populations. We found significant differences between populations in metazoan parasites, neutral and adaptive genetic diversities. The analyses based on pairwise data revealed that populations with dissimilar MHC allelic profiles were geographically distant populations with significantly different diversity in microsatellites and a dissimilar composition of parasite communities. The results from the generalized estimating equations method (GEE) on the level of individuals revealed that metazoan parasite load in European chub was influenced by the diversity of DAB alleles as well as by the diversity of neutral genetic markers and host traits reflecting condition and immunocompetence. The multivariate co-inertia analysis showed specific associations between DAB alleles and parasite species. DAB1-like alleles were more involved in associations with ectoparasites, while DAB3-like alleles were positively associated with endoparasites which could suggest potential differences between DAB genes caused by different selection pressure. Our study revealed that parasite-mediated selection is not the only variable affecting MHC diversity in European chub; however, we strongly support the role of neutral processes as the main driver of DAB diversity across populations. In addition, our study contributes to the understanding of the evolution of MHC genes in wild living fish.
Keywords: Animals; Europe; paraziti; selekce (genetika); Cyprinidae; nemoci ryb; divoká zvířata; Evropa; hlavní histokompatibilní komplex; Fish Diseases; Host-Parasite Interactions; Parasitic Diseases, Animal; interakce hostitele a parazita; Major Histocompatibility Complex; Selection, Genetic; Parasites; Genetic Variation; parazitární nemoci u zvířat; Animals, Wild; Microsatellite Repeats; alely; Alleles; zvířata; genetická variace; mikrosatelitní repetice